Fabrication of grooved LGS resonators based high temperature SAW sensors and analysis with FEM simulation. (1st October 2022) - Shan, Qingchuan; Shi, Ruchuan; Zhang, Qilun; Hao, Wenchang; Luo, Wei; Han, Tao
Abstract: Langasite (LGS) based surface acoustic wave (SAW) sensors are widely used in high temperature circumstances due to their advantages of being passive and wireless. In this research, the platinum electrodes are deposited into the grooves of the LGS instead of on the surface to further improve the acoustic properties and prolong the lifetime of the resonators at high temperature. Proper MEMS fabrication techniques are proposed to fabricate such structures. The result of every step is evaluated, and the corresponding process parameters are optimized. With the optimal processes, two types of resonators with different Euler angles of (0 ∘, 22 ∘, 30 ∘ ) and (0 ∘, 22 ∘, 90 ∘ ) are fabricated on the LGS substrate. Furthermore, the process-influenced structure parameters such as metal ratio and sidewall angle are well investigated via a weak form nonlinear finite element method simulation model. The temperature dependence of the resonance frequency is measured, and the recorded thermal behaviors match well with the prediction of the simulation. In addition, the further endurance test shows that the devices could work at 1000 ∘ C for 12 h. This research proves the validity of the grooved resonator structure and the prominent role of the simulation model in further optimizing the LGS-based SAW devices design.